Modelos de Schwinger, Thirring e Kondo à temperatura finita: um estudo - Oliveira, R. de [UNESP] (2007)
We study the thermodynamical properties of some bidimensional Quantum Field Theories: the Schwinger model, Thirring model and the gauged Thirring model. The study is based on the systematic application of the Dirac's formalism for constrained systems with the intention of establishing the Partition function via the functional integration formalism